Interoception Dysfunction Contributes to the Negative Emotional Bias in Major Depressive Disorder - Zhou, Hongliang; Zou, Haowen; Dai, Zhongpeng; Zhao, Shuai; Hua, Lingling; Xia, Yi; Han, Yingling; Yan, Rui; Tang, Hao; Huang, Yinghong; Du, Yishan; Wang, Xiaoqin; et al. (Frontiers in Psychiatry, 2022)
Background: Previous researches have demonstrated that impaired interoception is involved in emotional information processing in major depressive disorder (MDD). Heartbeat-evoked potential (HEP) amplitudes, an index for interoception, could be manipulated by emotional faces in healthy people. Considering negative emotional bias is the core characteristic in MDD, we hypothesized that interoception dysfunction was associated with the negative emotional bias in MDD. Method: An electroencephalogram (EEG) study under an emotional faces task was applied to explore the relationship between interoception and emotional bias. HEPs before emotional faces stimuli were used to predict the late positive potential (LPP) amplitudes and it worked as an index of emotional bias. Twenty-seven patients with MDD (MDDs) and 27 healthy controls (HCs) participated in this study. Source analysis gave an auxiliary description for results in sensory level. Results: MDDs had poor performance in heartbeat count task (HCT) and attenuate HEP average amplitudes (455 - 550 ms). Compared with HCs, cluster-based permutation t tests revealed that MDDs had attenuated LPP amplitudes (300 - 1000 ms) over centroparietal regions and enhanced LPP amplitudes over frontocentral regions. Furthermore, abnormal attenuated HEPs could predict aberrant LPPs under sad face stimuli in MDDs, which could be associated with the dysfunction of anterior cingulate cortex (ACC) and right insula. Conclusion: Mediated by ACC and insula, interoception dysfunction contributes to the negative emotional bias of MDD, highlighting the importance of interoception in the disorder.